2009
DOI: 10.1590/s1980-57642009dn30100005
|View full text |Cite
|
Sign up to set email alerts
|

Stroke and brain atrophy in chronic Chagas disease patients: A new theory proposition

Abstract: Chagas disease (CD) remains a major cause of cardiomyopathy and stroke in developing countries. Brain damage in CD has been attributed exclusively to the effects of structural heart disease on the brain, including cardioembolism and low cardiac output symptoms. However, CD patients also develop stroke and brain atrophy independently of cardiac disease severity. Chronic inflammation directed against T. cruzi may act as a trigger for endothelial damage, platelet activation, acceleration of atherosclerosis and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
0
9
0
4
Order By: Relevance
“…Both IL-6 and TNF-alfa production are associated with chronic Chagas disease [4,5]. Thus, we hypothesize that chronic inflammation in Chagas disease may underlie the mechanism for a progressive form of brain atrophy [8].…”
Section: Discussionmentioning
confidence: 89%
“…Both IL-6 and TNF-alfa production are associated with chronic Chagas disease [4,5]. Thus, we hypothesize that chronic inflammation in Chagas disease may underlie the mechanism for a progressive form of brain atrophy [8].…”
Section: Discussionmentioning
confidence: 89%
“…Thus, all patients with cryptogenic or cardioembolic stroke should be screened for T. cruzi infection if they live in or have emigrated from endemic areas, mainly South America 30 . Chronic inflammation in CD has been hypothesized as a trigger to cause vascular damage and stroke in this group of cryptogenic stroke patients with no significant systolic dysfunction or cardiac arrhythmias 31 .…”
Section: Cardiogenic Embolismmentioning
confidence: 98%
“…In terms of pathways, KEGG pathway enrichment analysis results show that 65 key targets are also significantly enriched in diseases-related pathways such as herpes virus infection, hepatitis B, cancer, diabetes, and Chagas disease, suggesting that there may be correlations and effects between different diseases, Which has also been verified in previous research.Studies have shown that the hepatitis B core antibody (anti-HBc) positive / hepatitis B surface antigen (HBsAg) negative pattern is associated with intracranial atherosclerotic stenosis in hepatitis B virus infection [51] .In virologically suppressed HIV patients, human herpesvirus 8 (HHV-8) infection increases inflammation and activates immunity, increasing the risk of atherosclerosis [52] .With common risk factors, cancer and atherosclerosis have the same basis as metabolic or vascular abnormalities,and the theory of inflammation is the common pathological basis of both them [53] .Chronic inflammation caused by Chagas disease may trigger endothelial damage and platelet activation, accelerating atherosclerosis [54] .In the progression of atherosclerosis, the PI3K-Akt signaling pathway plays an important role in the survival, proliferation and migration of macrophages [55] ,which suggesting that HLJDD may prevent atherosclerosis by regulating PI3K-Akt signaling pathway and inhibiting the related effects of macrophages.Signaling pathways such as IL-17 signaling pathway and TNF signaling pathway are closely related to inflammatory response. Activation of IL-17 signaling pathway and TNF signaling pathway can activate downstream NF-κ B signaling pathways, leading to the production of various mediators associated with atherosclerosis, including inflammatory factors ,chemokines and others [56][57] .…”
Section: Figure7hljdd-key Active Ingredients-key Targets-pathway Netmentioning
confidence: 99%